What happens to extension institutions during disease outbreaks and how to prevent institutional capacity erosion - Babu, Suresh Chandra (United States Agency for International Development, 2020)
Natural disasters and disease outbreaks deeply impede the progress developing countries make in achieving the Sustainable Development Goals (SDGs). Situations such as these affect the food and agricultural sector in a large way, directly affecting millions of rural households. Shocks to the agricultural and food systems impact countries through several pathways including diversion of institutional and human resources toward emergency operations.